MAINTENANCE OF JAVANESE JONEGOROAN LANGUAGE IN BOJONEGORO STUDENTS IN BRAWIJAYA UNIVERSITY, MALANG - Maulidia Tifani Alfin Nur Hardiana (ppjbsip, 2020)
Javanese of East Java dialect has several subdialects, one of which is the Jonegoroan subdialect. Jonegoroan Javanese Language (BJJ) is still spoken by a group of Bojonegoro students in the University of Brawijaya Malang in their daily communication. This study aims to 1) interpret language cases; 2) variation patterns, and 3) reveal the reason for the use of BJJ by Bojonegoro students in UB Malang. This research is a qualitative descriptive study. Data collection uses observation, interview, recording, and listening techniques. Data analysis in this study used a sociolinguistic approach with several theories, including the theory of language retention and the theory of word change. The results of this study are 1) cases of linguistics that often arise in speech use are apheresis; 2) BJJ variation patterns include forms of suffix changes and several other terms that are distinguishing or indicating BJJ identity toward Javanese in other regions; and 3) the reasons for saying BJJ is expression of regional spirit, compulsion, bonding solidarity, ethnic existence, ease of communication, habits, pride, awareness of norms, and language loyalty.